Internet Economy vs Classic Economy: Struggle of Contradictions - Sukhodolov, Alexander P.; Popkova, Elena G.; Kuzlaeva, Irina M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This unique book adopts a problem approach to study the Internet economy, which consists in assessing its contradiction to classic economy, analyzing it, and describing how the Internet economy is developing in modern Russia. The authors study its sense and basic principles, identify the factors that influence its functioning and development, analyze the crisis of the Internet economy, and conduct a comparative analysis of the Internet economy and classic economy. The book is primarily intended for postgraduates, educators and researchers who study the foundations of the modern macro-economy. Based on the conclusions and results presented here, they will be able to create their own scientific studies. Further, problem analysis of the Internet economy and classic economy makes it possible to identify the peculiarities and prospects of development, and to form recommendations for the highly effective management of modern economic systems.
Production and Economic Relations on the Internet: Another Level of Development of Economic Science -- Internet Economy: Existence from the Point of View of Micro-Economic Aspect -- Perspectives of Internet Economy Creation -- Modern Foundations of Internet Economy.
Keywords: Computational intelligence; Econometrics; Computational Intelligence; Quantitative Economics